Percepção sobre botânica entre estudantes de diferentes faixas etárias em escolas da educação básica no Oeste do Pará. - (:unkn) unknown (UNIVERSIDADE FEDERAL DO OESTE DO PARÁ, 2024)
The concept of "Botanical Blindness" refers to the difficulty in perceiving and valuing plants. "Botanical Imperception" expands on this idea, considering psychological, environmental, and social factors that contribute to this disconnection. The lack of adequate botanical education in schools intensifies this devaluation, while there is a disproportionate emphasis on Zoology. This study aimed to investigate the environmental perceptions and attitudes of children, teenagers, and adults in the school context, with the objective of determining whether there are differences in how children, teenagers, and adults enrolled in educational institutions perceive the nature around them, as well as the vegetation around them as a living presence. The methodology used was field research, conducted in two rural schools and two urban schools in the city of Santarém, PA, with a questionnaire containing 12 questions, 10 of which were objective and 2 subjective, serving as an important tool for both qualitative and quantitative evaluation. A total of 508 students responded to the questionnaire. Through analysis of the results, a greater distance from nature was observed among adults. Children demonstrated lower perception of nature compared to teenagers and adults, while teenagers exhibited the highest perception among the groups. Children's knowledge of plants was the lowest, while teenagers demonstrated the highest knowledge; however, in general, the types of plants participants were familiar with were those present in their homes. The most commonly cited types of plants were edible, medicinal, and ornamental. Thus, it can be noted that the participants' overall perception of nature is low, but their knowledge of plants is relatively high, largely due to the plants they encounter in their daily lives at home. In this context, if schools act as agents that build on the knowledge students bring from home and apply methodologies that spark their interest, students' perceptions of nature, and especially plants, can gradually improve.
Keywords: Impercepção botânica; Faixa etárias; Escola; CIÊNCIAS BIOLÓGICAS